Functional Change in the Caudal Pontine Reticular Nucleus Induced by Age-Related Hearing Loss - Ning Zhao; Ana’am Alkharabsheh; Fei Xu; Wei Sun (Neural Plasticity)
Increased acoustic startle responses (ASR), which represent reduced uncomfortable loudness level in humans, have been reported in middle-aged C57BL/6J mice with sensorineural hearing loss. Although neural plasticity changes in the central auditory system after the peripheral lesions were suggested to underlie this phenomenon, the neurological cause of exaggerated ASR is still not clear. In this study, the local field potentials and firing rates of the caudal pontine reticular nucleus (PnC), which plays a major role in the ASR pathway, were recorded in 2-month- and 6-month-old C57BL/6 J mice. Consistent with our previous studies, the amplitude of ASR increased, and the threshold of ASR decreased in the 6-month-old mice after developing 20–40 dB hearing loss. The PnC response induced by high-frequency stimuli (>20 kHz) decreased in the 6-month group, whereas the PnC response induced by low-frequency stimuli (<12 kHz) showed a significant increase in the 6-month group compared to the 2-month group. The enhancement of PnC response is similar to the ASR increase found in the 6-month-old C57 mice. Our results suggest that the high-frequency hearing loss caused an increase in PnC sensitivity in the C57 mice which may enhance ASRs.